(untitled) (Basel Media Culture and Cultural Techniques Working Papers, 2025)
Taking a cue from, and echoing, the oft-repeated call in media studies to move from studying media to mediation, this keyword-memo suggests concretion as a possible critical term in media theory today. In doing so, it tracks a speculative deep history of concretion, reflects upon the limited kinds of argumentations available to scholars in the field today, and argues that contemporary media studies lacks the vocabulary to deal with state changes, such as those between ideas/ideologies and the materialities of technics. The provocation then is to think with the unifying possibilities that con-cretion might offer us as an agglomeration of conceptual frameworks.